10 Answered Questions for the topic Circle Equation

Circle Equation

05/21/17

#### A circle has a radius of √37 units and is centered at (1.3,−3.5 ). write the equation of this circle.

I dont know how to write the equation.

Circle Equation

03/07/17

#### You have two circular flower beds, as shown. The sum of the areas of the two flower beds is 136π square feet. Find the radius of each bed.

Big flower bed = r ft
Small flower bed = (r-4) fy

Circle Equation

02/03/16

#### find the diameter

the locus of the point of intersection of perpendicular tangents drawn to each of circles x2 + y2 = 16 and x2 + y2 = 9 is a circle whose diameter is
(I)5
(ii)√7
(iii)2√7
(iv)10

Circle Equation

02/03/16

#### angle between tangents

if two tangents are drawn from a point on x2 + y2 = 16 to the circle x2 + y2 = 8 then the angle between the tangents is
(I)900
(ii)450
(iii)1200
(iv)1800

Circle Equation

02/03/16

#### find the locus

locus of point of intersection of perpendicular tangents drawn one to each of the circles x2 + y2 = 8 and x2 + y2 =12 is
(I) x2 + y2 = 4
(ii)x2 + y2 = 20
(iii)x2 + y2 = 208
(iv)x2 + y2 = 16

Circle Equation

02/07/15

#### Consider the following circle: (x+1)^2 + (y-1)^2 =2

What is the slope-intercept form of the line that is tangent to the circle and passes through the origin?

#### Circle Equation

2 x^2+4 x+2 y^2+12 y = 20 is the equation of a circle with and can be written in the general form (x-h)^2 + (y-k)^2 = r^2. Find h, k, and r.

#### Circle Question

Recall the equation for a circle with center (h,k) and radius r. At what point in the first quadrant does the line with equation y = 1 x + 4 intersect the circle with radius 4 and center (0, 4)?
more

#### Circle Equation

Find an equation of the circle with center at (4,-6) that is tangent to the y-axis in the form of (x-A)^2+(y-B)^2=C where A, B, C are constant.
What is A, B & C?

Circle Equation Circles

10/07/14

#### Circle Equation

Find an equation of the circle with center at (4,-6) that is tangent to the y-axis in the form of (x-A)^2+(y-B)^2=C where A, B, C are constant.

## Still looking for help? Get the right answer, fast.

Ask a question for free

Get a free answer to a quick problem.

Most questions answered within 4 hours.

#### OR

Find an Online Tutor Now

Choose an expert and meet online. No packages or subscriptions, pay only for the time you need.